(untitled) (Journal of Philosophy Culture and Political Science, 2023)
Abstract. This article examines the meaning of the concept of "Justice" in Yūsuf Khāss Hājib’s poem «Kutadgu Bilig» («Wisdom of Royal Glory»). The main goal of the article is to analyze Yūsuf Khāss Hājib’s thoughts on the concept of "Justice" and to determine their compatibility with the views of Abū Naṣr Muḥammad al-Fārābī as well as their continuity with the ideas of "New Kazakhstan" and “Just State” proposed by the President of Kazakhstan K.-Zh. Tokayev. As a result of the analysis of "Kutadgu Bilig", it was determined that the concept of "justice" is described as the main principle of ethical regulation of social relations as well as an essential quality of a person (first ruler) that brings justice and happiness to people. Moreover, Yūsuf Khāss Hājib wrote his work intending to create a new generation of political leaders to bring happiness and equality to his or her people and establish a just and virtuous society. Furthermore, the comparative analysis of the views of Yūsuf Hass Hajib and al-Fārābī about "Justice" and "Just society" revealed that their views are harmoniously related to each other. In the doctrine of al-Fārābī on political leadership, the concept of "Justice" is also described as one of the essential qualities of the “first ruler.” The comparative analysis also reveals the succession of views of two great thinkers regarding the concept of "Justice" with the current ideological programs being implemented in Kazakhstan. The results of the article can be used as a theoretical and methodological basis for deep analysis and disclosure of new aspects of the social and political teachings of two great scholars, Yūsuf Khāss Hājib and al-Fārābī. Keywords: Turkic thinkers, Turkic philosophy, al-Fārābī, Yūsuf Khāss Hājib, "Kutadgu Bilig" ("The Wisdom of Royal Glory), Justice, "Just State," "New Kazakhstan."